Analisis Kelalaian Perusahaan PT Indonesia Morowali Industrial Park (PT. IMIP) terhadap Keselamatan Pekerja PT Indonesia Thingshan Stainless Stell (ITSS): Study Kasus Ledakan Tungku Smelter pada PT IMIP - Sur Fadila; Alifia Nur Iddhiyan; Nur Arifudin; Ziana Walidah; Desi Wilda Rizki Amelia (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
The accident at the smelter furnace at PT Indonesia Morowali Industrial Park (PT IMIP) raised questions about work safety at the company. It is known that there is negligence in implementing Occupational Safety and Health (K3) regulations at PT IMIP, especially regarding the use of Personal Protective Equipment (PPE) whose quality and use does not comply with PPE standards. PT IMIP failed to ensure that PT Indonesia Thingshan Stainless Stell (ITSS) complied with K3 regulations, which resulted in a fatal accident, namely the explosion of the smelter furnace which resulted in 51 victims. Based on the results of research using normative juridical methods, it is stated that PT IMIP must be responsible for the accident, in accordance with applicable laws and regulations, namely Law Number 13 of 2003 concerning Employment, Law Number 1 of 1970 concerning Safety Work, and other derivative regulations. This incident emphasizes PT IMIP's negligence regarding the importance of implementing K3 regulations and the company's responsibility for work safety. Although compensation has been provided to the victim's family, improvements in the K3 system are expected to prevent similar accidents in the future.